Axial spondyloarthritis in patients with recurrent fever attacks: data from the AIDA network registry for undifferentiated autoInflammatory diseases (USAIDs) - Vitale, Antonio; Caggiano, Valeria; Silva, Isabel; Oliveira, Daniel G.; Ruscitti, Piero; Ciccia, Francesco; Vasi, Ibrahim; Tufan, Abdurrahman; Lopalco, Giuseppe; AlMaghlouth, Ibrahim A.; Sota, Jurgen; Wiesik-Szewczyk, Ewa; et al. (Frontiers in Medicine, 2023)
Beckground: despite the recent advances in the field of autoinflammatory diseases, most patients with recurrent fever episodes do not have any defined diagnosis. The present study aims at describing a cohort of patients suffering from apparently unexplained recurrent fever, in whom non-radiographic axial spondylarthritis (SpA) represented the unique diagnosis identified after a complete clinical and radiologic assessment. Materials and methods: patients’ data were obtained from the international registry on Undifferentiated Systemic AutoInflammatory Diseases (USAIDs) developed by the AutoInflammatory Disease Alliance (AIDA) Network. Results: a total of 54 patients with recurrent fever episodes were also affected by non-radiographic axial SpA according to the international classification criteria. SpA was diagnosed after the start of fever episodes in all cases; the mean age at the diagnosis of axial SpA was 39.9±14.8 years with a diagnostic delay of 9.3 years. The highest body temperature reached during flares was 42°C, with a mean temperature of 38.8±1.1 °C. The most frequent manifestations associated to fever were: arthralgia in 33 (61.1%) cases, myalgia in 24 (44.4%) cases, arthritis in 22 (40.7%) cases, headache in 15 (27.8%) cases, diarrhea in 14 (25.9%) cases, abdominal pain in 13 (24.1%) cases, and skin rash in 12 (22.1%) cases. Twenty-four (44.4%) patients have taken daily or on-demand non-steroidal anti-inflammatory drugs (NSAIDs) and 31 (57.4%) patients have been treated with daily or on demand oral glucocorticoids. Colchicine was used in 28 (51.8%) patients, while other conventional disease modifying anti-rheumatic drugs (cDMARDs) were employed in 28 (51.8%) patients. Forty (74.1%) patients underwent anti-tumor necrosis factor (TNF) agents and 11 (20.4%) were treated with interleukin (IL)-1 inhibitors. The response to TNF inhibitors on recurrent fever episodes appeared more effective than that observed with anti-IL-1 agents; colchicine and other cDMARDs were more useful when combined with biotechnological agents. Conclusions: signs and symptoms referring to axial SpA should be inquired in patients with apparently unexplained recurrent fever episodes. The specific treatment for axial SpA may lead to a remarkable improvement in the severity and/or frequency of fever episodes in patients with unexplained fevers and concomitant axial SpA.